2010
DOI: 10.1213/ane.0b013e3181e4255f
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Cross-Clamping and Reperfusion in Pigs Reduces Microvascular Oxygenation by Altered Systemic and Regional Blood Flow Distribution

Abstract: Increased systemic and regional blood flow and oxygen supply after ACC does not ensure adequate regional blood flow and microcirculatory oxygenation in all organs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 29 publications
3
30
1
Order By: Relevance
“…Using LSCI for microcirculatory blood flow evaluation of the terminal ileum together with macrohaemodynamic measurements, impairment of intestinal microcirculation was observed accompanied by a decline in MAP, SV, and CO 6 h after I/R. This microcirculatory behavior is in line with the results of Siegemund et al, 25 who showed a reduction of serosal microcirculatory oxygenation and perfused ileal capillaries 3 h after I/R and has been reported for other organs as well. 18,26 Simultaneous examination of macrohaemodynamic parameters and intestinal microcirculation during volume administration shows dissociation between micro-and macrocirculatory blood flow.…”
Section: Color-picturesupporting
confidence: 87%
“…Using LSCI for microcirculatory blood flow evaluation of the terminal ileum together with macrohaemodynamic measurements, impairment of intestinal microcirculation was observed accompanied by a decline in MAP, SV, and CO 6 h after I/R. This microcirculatory behavior is in line with the results of Siegemund et al, 25 who showed a reduction of serosal microcirculatory oxygenation and perfused ileal capillaries 3 h after I/R and has been reported for other organs as well. 18,26 Simultaneous examination of macrohaemodynamic parameters and intestinal microcirculation during volume administration shows dissociation between micro-and macrocirculatory blood flow.…”
Section: Color-picturesupporting
confidence: 87%
“…Kidney tissue P o 2 has been directly quantified in animal models of AKI induced by radiocontrast administration, renal ischaemia–reperfusion, endotoxaemia and rhabdomyolysis . These studies confirm that the tissue is hypoxic, although studies using less direct methods, such as blood oxygen‐dependent magnetic resonance imaging (BOLD MRI), have not always confirmed the presence of hypoxia in some models .…”
Section: Haemodynamic Factors and Renal Hypoxia In Acute Kidney Injurmentioning
confidence: 99%
“…In rats with 30 minutes of ischemia, RBF and cortical and medullary oxygenation were persistently reduced at 3 hours after reperfusion [22]. Similarly, in pigs with 45 minutes of aortic cross-clamping, reduced oxygenation and persistent hypoxia at 4 hours of reperfusion was observed [23]. Using MRI in rats before and after 45 minutes of ischemia followed by reperfusion for approximately 100 minutes, global reduction in tissue oxygenation during ischemia was observed [24].…”
Section: Ischemia-reperfusionmentioning
confidence: 99%